Hubungan Karakteristik dan Tekanan Sosial dengan Perilaku Berisiko Penularan HIV/AIDS - Sri Mindayani; Hilda Hidayat (Jurnal Riset Hesti Medan, 2019)
HIV / AIDS in Indonesia was concentrated in certain population groups (key populations) who have a high risk of HIV transmission related to their behavior, one of which is loading worker. This study aims to determine the relationship of characteristics and social pressures with risk behaviors of HIV / AIDS transmission in loading workers in Port of Padang City. This type of research was analytic with cross sectional design. This research was conducted from January - April 2019 at the Port of Padang City. The study population numbered 834 people and a sample of 90 people. Sampling was done by cluster sampling technique. Primary data collection is done by interview using a questionnaire. Data analysis includes univariate analysis and bivariate analysis. The results showed no relationship between age, education, and ethnicity with HIV/AIDS risk behavior in loading workers. There was a relationship between social pressure and HIV/AIDS risk behavior in loading workers. It is recommended to Koperbam to provide information routinely on HIV / AIDS risk behavior in loading workers. It is also recommended that Koperbam cooperate with the local health center to carry out an HIV check.